Decadal evolution of a spit in the Baram river mouth in eastern Malaysia - Ramasamy, Nagarajan; Jonathan, M.; Roy, P.; Muthusankar, G.; Lakshumanan, C. (Elsevier Ltd, 2015)
We studied a newly formed spit in the Baram River mouth in Eastern Malaysia and evaluated the effects of climatic conditions and human interference over the last four decades (1974-2014). The development of a spit during a decade (1998-2008) and its maximum expansion over the period 2005-2010 is related to the erosion associated with deforestation and land use changes in the upstream region. The downstream transportation of the heavy sediment load occurred during the events of higher precipitation and flash floods. The recent spit was identified for the first time as a mud flat post the flash flooding of January 2005. It extended towards the south west of the river mouth till 2010 (six fold increase in area from 2005 to 0.29km2) and gradually disintegrated over the next 3 years. Depositional feature of coarse sediments and organic debris is clearly supported by the alternating thick layers in the top 25cm of the three core samples (C1-C3) collected from the region. The non-existence of finer particles clearly indicates the supremacy of long shore currents in the region carrying away the fines to deeper regions. Gradual disappearance of the sand barrier post 2011 is due to the reduction in the amount of sediment load as a result of reduction in recent rainfall activity, land use/land cover changes mainly as reforestation, strengthening of palm plantation (controlling soil erosion in the river banks) in the upstream region. The dominant NW wind direction during the major part of the year is also one of the factors for the shift in depositional sequence and it is helped by the long shore currents which lead to the spit being partially connected to the main land.